Keprakan Gaya Surakarta - Widodo Widodo (Lakon Jurnal Pengkajian & Penciptaan Wayang, 2020)
The study activities of the students of Puppetry Department of ISI Surakarta, especially in the teaching and learning process of the Pedalangan Gaya Pokok course, use pakeliran karawitan music in the form of keprakan. There are problems in the form of a lack of reference materials related to the accompaniment of keprakan music so that it is not appropriate in its application. So this study seeks to describe and notate the keprakan of Surakarta style so that it can be used as a guide for students. The results of this description and notation are expected to help, facilitate and provide information to students to produce good practice.